EXPLORING OF PHYSICS CONCEPTS OF “SOUND WAVES” IN THE MORONENE TRIBE'S TAMBURU MUSICAL INSTRUMENT AS A PHYSICS LEARNING MATERIAL - NABA, SUL DAENG; KUSWANTO, HERU; KURNIAWAN, ARIS; ADRIANTO, NANANG (SCIENCE : Jurnal Inovasi Pendidikan Matematika dan IPA, 2024)
This research investigates the physics concepts embedded in the traditional musical instrument "Tamburu" of the Moronene tribe in Southeast Sulawesi, Indonesia. The Tamburu, a traditional plucked string instrument made from layers of bamboo bark, serves as a fascinating case study for exploring physics concepts. The research aims to uncover the connections between the physics concepts applied to this traditional cultural instrument. The methodology combines observational analysis, video recording, and theoretical physics calculations to provide a comprehensive understanding of the sound waves involved in the Tamburu. The results reveal intricate connections between interrelated physics principles, demonstrating how traditional local wisdom can provide explanations for complex scientific knowledge. The research found several connections between physics concepts in the Tamburu, including the concept of sound sources, types of sound waves, frequency, tone (timbre), resonance, and open organ pipes. This research not only highlights the significance of the local culture of the Tamburu but also emphasizes its potential in the field of education as a means of teaching and understanding physics in real-world contexts. This research seeks to integrate the heritage of local wisdom into the educational framework to enrich learning experiences and introduce a deeper appreciation for indigenous knowledge systems.